Advanced risk analysis in engineering enterprise systems - Pinto, Cesar Ariel; Garvey, Paul R., 1956- (Boca Raton : CRC Press, 2013)
"Preface Engineering today's systems is a challenging and complex task. Increasingly, systems are engineered by bringing together many separate systems, which together provide an overall capability that is otherwise not possible. Many systems no longer physically exist within clearly defined boundaries, are characterized by their ubiquity and lack of specification, and are unbounded, for example, the Internet. More and more communication systems, transportation systems, and financial systems connect across domains and seamlessly interface with an uncountable number of users, information repositories, applications, and services. These systems are an enterprise of people, processes, technologies, and organizations. Enterprise systems operate in network-centric ways to deliver capabilities through richly interconnected networks of information and communication technologies. Engineering enterprise system is an emerging discipline. It encompasses and extends traditional systems engineering to create and evolve webs of systems and systems-of-systems. In addition, engineering management and management sciences communities need new approaches for analyzing and managing risk in engineering enterprise systems. The aim of this book is to present advances in methods designed to address this need. This book is organized around a set of advanced topics in risk analysis that are related to engineering enterprise systems. They include the following: A risk analytical framework for engineering enterprise systems Capability portfolio risk management Functional dependency network analysis (FDNA) Extreme-event theory Prioritization systems in highly networked enterprise environments Measuring risks of extreme latencies in complex queuing networks"--
1. Engineering risk management -- 2. Perspectives on theories of systems and risk -- 3. Foundations of risk and decision theory -- 4. A risk analysis framework in engineering enterprise systems -- 5. An index to measure risk corelationships -- 6. Functional dependency network analysis -- 7. A decision-theoretic algorithm for ranking risk criticality -- 8. A model for measuring risk in engineering enterprise systems -- 9. Random processes and queuing theory -- 10. Extreme event theory -- 11. Prioritization systems in highly networked environments -- 12. Risks of extreme events in complex queuing systems.
"A Chapman & Hall book."
Includes bibliographical references and index.
Also available as an electronic resource.
Keywords: Reliability (Engineering); Technology -- Risk assessment; Systems engineering